ANALISIS FAKTOR YANG MEMENGARUHI PROFITABILITAS PADA PERUSAHAAN SEKTOR PROPERTY & REAL ESTATE DI BEI PERIODE 2019-2024 - RIKARDA CHIKA MARCELLA HARIJANTO; AGUSTINUS SRI WAHYUDI (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2025)
This research aims to examine whether internal factors influence corporate profitability. The internal factors that are analyzed to influence profitability are firm efficiency, firm growth, leverage, liquidity, and firm size. The objects focuses on property and real estate companies listed on the Indonesia Stock Exchange (IDX) during the 2019–2024 period. This study uses secondary data and applies purposive sampling, resulting in 84 observations from 14 companies that met the sample criteria. The analysis method employed is multiple linear regression using the EViews 12 software. The results indicate that firm efficiency and firm growth have a positive effect on profitability, while leverage has a negative effect. Meanwhile, liquidity and firm size do not have a significant effect on profitability.